COMPUTER ASSISTED LANGUAGE LEARNING THROUGH ENGLISHCLASS101.COM: TO UNRAVEL THE UNDERPINNING METHODOLOGY - Maakh , Yeri Nofita; Jonathans, Peggy Magdalena (English Education Study Program - Artha Wacana Christian University, 2023)
English Language Teaching (ELT) is supposed to assist learners in actual life at the marketplace. Computer Assisted Language Learning (CALL) globally has flourished with tremendous products to address the purpose, e.g., EnglishClass101.com. Though this website includes a few aspects of ELT, the learning platform draws our attention for its affordability of price, feasibility of use, and recency of topics. The present study aims to unravel the underpinning teaching methodology of the website, with a particular focus on English grammar teaching. The present study employs a qualitative study design with two instruments of data collection: observation and transcription of lesson videos. The results indicate that contextual English grammar was used and integrated with lessons (newest and favorite); vocabulary (lists, words of the day, common words, key phrases); teacher assistance (explanation, assessment, tests). Majorly, two methods have been elaborated throughout the lessons on the website, i.e., Communicative Language Teaching, and Direct Method. Additionally, a few techniques are performed including teachers' gestures for meaning, annotation, repetition, drill, elicitation, option matching, deductive and inductive approach. The findings imply that any CALL products remain in use when the aspects of lessons involve daily topics and select feasible ELT methods